PENGARUH KUALITAS PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI KANTOR BADAN KESATUAN BANGSA DAN POLITIK KOTA SAMARINDA - Selfiyani, Reny (PREDIKSI, 2014)
ABSTRACTÂ Data were collected through questionnaires to 40 respondents Kesbang Politik Kota Samarinda Employees District Office. The collected data were analyzed by simple linear regression using SPSS for windows.The results of the data analysis showed that the quality of employees have a positive and significant impact on Employee Job Performance Across Kesbang Politik Kota Samarinda District Office, having known R count 0.604> 0.312 R table, and value significance of 0000 is less than 0.05.Rated R Square of 36.5 percent, meaning that employees can affect the quality of Employees Occupational Performance Across the District Office Kesbang Politik kota Samarinda of 36.5 percent, while the remaining 63.5 percent were not influenced by other variables examined in this study.